Diesel exhaust particles induce autophagy and citrullination in Normal Human Bronchial Epithelial cells. Issue 11 (November 2018) - Colasanti, Tania; Fiorito, Silvana; Alessandri, Cristiano; Serafino, Annalucia; Andreola, Federica; Barbati, Cristiana; Morello, Francesca; Alfè, Michela; Di Blasio, Gabriele; Gargiulo, Valentina; Vomero, Marta; Conti, Fabrizio; et al.
Abstract A variety of environmental agents has been found to influence the development of autoimmune diseases; in particular, the studies investigating the potential association of systemic autoimmune rheumatic diseases with environmental micro and nano-particulate matter are very few and contradictory. In this study, the role of diesel exhaust particles (DEPs), one of the most important components of environment particulate matter, emitted from Euro 4 and Euro 5 engines in altering the Normal Human Bronchial Epithelial (NHBE) cell biological activity was evaluated. NHBE cells were exposed in vitro to Euro 4 and Euro 5 particle carbon core, sampled upstream of the typical emission after-treatment systems (diesel oxidation catalyst and diesel particulate filter), whose surfaces have been washed from well-assessed harmful species, as polycyclic aromatic hydrocarbons (PAHs) to: (1) investigate their specific capacity to affect cell viability (flow cytometry); (2) stimulate the production of the pro-inflammatory cytokine IL-18 (Enzyme-Linked ImmunoSorbent Assay -ELISA-); (3) verify their specific ability to induce autophagy and elicit protein citrullination and peptidyl arginine deiminase (PAD) activity (confocal laser scanning microscopy, immunoprecipitation, Sodium Dodecyl Sulphate-PolyAcrylamide Gel Electrophoresis -SDS-PAGE- and Western blot, ELISA). In this study we demonstrated, for the first time, that both Euro 4 and Euro 5 carbon particles, deprived of PAHs possibly adsorbed on the soot surface, were able to: (1) significantly affect cell viability, inducing autophagy, apoptosis and necrosis; (2) stimulate the release of the pro-inflammatory cytokine IL-18; (3) elicit protein citrullination and PAD activity in NHBE cells. In particular, Euro 5 DEPs seem to have a more marked effect with respect to Euro 4 DEPs.